Electrical Engineering for Non-Electrical Engineers. - Rauf, S. Bobby, 1956- (River Publishers, 2021)
Engineers and non-engineers often eschew electrical engineering because it is premised on concepts and mathematical techniques that are somewhat more abstract and elusive than those employed in disciplines like civil, mechanical, and industrial engineering. Yet, because of the ubiquitous nature of electrical and electronic equipment and devices, and the indispensable role electricity plays in various facets of lives, a basic understanding of electrical engineering is essential. Engineers and non-engineers find themselves interfacing with electrical apparatus and dealing with matters that permeate into the electrical realm. Therein lies the purpose and objective of this book. This edition includes numerous updated pictures, diagrams, tables, charts, graphs, and improved explanation of certain concepts.
Keywords: Electrical engineering.; elektronické knihy; electronic books